Influence of post-merger restructuring on organizational development - Joseph Madara (Ümit Hacıoğlu, 2021)
Corporate mergers are important for organizations to position themselves for growth and development. Stanbic Bank was formed as a result of a merger between CFC Bank and Stanbic Bank. Anecdotal evidence suggests that the merger has led to positive outcomes, but specific aspects of the merger that have contributed towards the organizational development of Stanbic Bank remain unclear. The study investigated the influence of Post-Merger Restructuring on the organizational development of Stanbic Bank Kenya. It was guided by efficiency theory and collected data from 27 branch managers and 9 senior sectional heads using a semi-structured questionnaire where a 75% response rate was achieved. Data were analyzed using descriptive and inferential statistics. Results showed that post-merger restructuring has a positive and statistically significant influence on organizational development at Stanbic Bank. The researcher concluded that post-merger restructuring had a positive influence on the organizational development of banks. The study recommends that banks should retrain their workforce, inculcate new culture, and redesign their operations in the post-merger period so as to realize the intended benefits.